Intraoperative distensibility measurement during laparoscopic Heller's myotomy for achalasia may reduce the myotomy length without compromising patient outcome. Issue 5 (13th March 2015) - Ilczyszyn, A.; Hamaoui, K.; Cartwright, J.; Botha, A.
Summary: Our study aimed to assess whether intraoperative esophagogastric junction (EGJ) distensibility measurement using the EndoFLIP EF325 catheter (Crospon Ltd., Galway, Ireland) could potentially be used to guide laparoscopic Heller's myotomy (LHM), potentially modifying the operation outcome and comparing this clinically to our previous technique of gastroscopic assessment. Following a full diagnostic assessment with manometry and endoscopy patients with achalasia were divided into two groups. A retrospective cohort of patients operated on between 2007 and 2010 had a gastroscopy‐guided LHM (G‐LHM) with a standardized myotomy of 8 cm on the esophagus and 3 cm on the stomach. From 2010, patients were prospectively studied with an EndoFLIP‐guided LHM (E‐LHM). The length of the myotomy was dictated by intraoperative distensibility monitoring of the EGJ. All patients with achalasia recorded Urbach quality of life scoring preoperatively and 6 months postoperatively. A further group of normal laparoscopic control patients (E‐LC) without any esophageal pathology also underwent intraoperative EGJ distensibility monitoring. Thirty‐eight patients took part, 15 in the E‐LC group, 8 in G‐LHM group and 15 in the E‐LHM group. We revealed that patients with achalasia in the E‐LHM group had a significantly smaller EGJ cross‐sectional area and distensibility than the E‐LC group. Myotomy and fundoplication increased the distensibility of the EGJ to a value greater than normal control patients. Patients in the G‐LHM group had a standard myotomy of 11 cm; patients in the E‐LHM group had a variable length myotomy of 6 cm (IQR 5.0–6.0). In both G‐LHM and E‐LHM groups, there was a significant improvement in patient's quality of life with no significant difference between the groups. Our study has shown that the EndoFLIP system was effective at measuring distensibility changes during LHM. LHM significantly increases the distensibility of the EGJ and also significantly improves patient symptoms. E‐LHM may reduce the overall myotomy length, and this does not appear to compromise the clinical outcome.